The Off-Line Simulation on Measuring through Software PC-DMIS CAD++ V4.3 - Vladimír Rudy; Marián Králik; Peter Malega; Naqib Daneshjo (Applied Sciences, 2021)
The article analyses and evaluates the ever-important topic of assessing geometric deviation of tolerated formations related to bases with the usage of coordinate measuring machines. The basic system for off-line simulation consists of the coordinate planes of a component’s coordinate system. At the beginning of the measurement, the coordinate system is created by the “3–2–1” alignment. Due to production deviations in real surfaces of the component, each measurement generates mutually different coordinate systems, which is well proven by the experiment on measuring with a coordinate measuring machine DEA Global Performance 12.22.10. An integral part of the article is also the quantification of geometric deviations of ideal tolerated formations related to bases, the estimate of the uncertainty of measurement arising from the placement of points in defining the base system, and the effect of such uncertainty upon the interval of satisfactory values in conformity with the STN EN ISO 14253-1 technical standard. The article also includes a proposal measure in order to ensure the reproducibility of defining the mutual position of coordinate systems.